Myeloperoxidase predicts risk of vasculopathic events in hemizgygous males with Fabry disease - Kaneski, Christine R.; Moore, David F.; Ries, Markus; Zirzow, G. C.; Schiffmann, Raphael (Neurology, 2006)
Fabry disease results in a global vasculopathy leading to early-onset stroke and renal and cardiac failure. We found that random myeloperoxidase in serum and plasma was significantly elevated in 73 consecutive male patients with Fabry disease. Random serum myeloperoxidase level in men predicted the risk of a Fabry vasculopathy-related event in subsequent years. Long-term enzyme replacement therapy did not reduce myeloperoxidase level or eliminate the risk of vasculopathic events.